Name-Title Entry Retrieval From a MARC File - Long, Philip L.; Kilgour, Frederick G. (Information Technology and Libraries, 1971)
A test of validity of earlier findings on 3,3 search-ke y retrieval from an in-process file for retrieval from a MARC file. Probability of number of entries retrieved per reply is essentially the same for both files.